ANALISIS SISTEM INFORMASI AKUNTANSI PENGGAJIAN DAN PENGUPAHAN DALAM UPAYA PENGENDALIAN INTERNAL PADA PT. GEMILANG EMAS INDONESIA - Langi, Brenda; Saerang, David P. E.; Gerungai, Natalia Y. T. (Universitas Sam Ratulangi, 2019)
Payroll and wages accounting information system are important in the enterprise systems that help in decision making and implementation of the payroll and wage employees. Internal control system is a system that protects wealth and enterprise accounting data. This study aims to determine how the payroll accounting information system and wage PT. Gemilang Emas Indonesia and whether the system supports the company's internal control efforts. Methods analysis used in this research is descriptive analysis. The results showed payroll accounting information system and wages in PT.Â Gemilang Emas Indonesia does not yet support the internal control efforts. Still a lack of segregation of duties in the organizational structure and practices of healthy companies.